Small Prime Modules and Small Prime Submodules - Mahmood, Layla S (Al-Nahrain Journal of Science, 2012)
Let R be a commutative ring with identity, and M be a unital (left) R-module. In this paper weintroduce and study the concepts: small prime submodules and small prime modules asgeneralizations of prime submodules and prime modules.Among the results that we obtain is the following:An R-module M is small prime if and only if the R-module R/annM is cogenerated by everynon-trivial small submodule of M.